Pollution Status of River Ramganga: Physico-chemical Characteristics at Bareilly - Adarsh Pandey2*, Ramesh Channdra1, kanchan kashyap1, and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The investigation is an effort to examine the impact of effluents discharged through industrial wastes and sewage into Ramganga and to observe the change in the quality of water for the period of different seasons of the year. Some physico-chemical parameters like temperature, pH, DO, Free CO2, TDS and TSS were studied and find the Site B was much polluted due to merging of a polluted tributary Nakatia. There DO was 3.07 mg/l and Free CO2was 26.69 mg/l. Key words: Ramganga river, water quality, Physico-Chemical parameters 1Department of Zoology, S.S.(P.G.)College, Shahjahanpur,U.P.; 2Department of Botany, S.S.(P.G.)College, Shahjahanpur,U.P Please Cite This Article As: Ramesh Channdra, kanchan kashyap, and Adarsh Pandey. 2010. Pollution Status of River Ramganga: Physico-chemical Characteristics at Bareilly. J. Exp. Sci. 1(5):20-21.